Complete chloroplast genome of eight Phaius (Orchidaceae) species from China: comparative analysis and phylogenetic relationship - Kaifeng Tao; Lu Tang; Yan Luo; Lu Li (BMC Plant Biology)
Abstract Background Phaius Lour. (Collabieae, Orchidaceae) is a small genus consisting of about 45 species, with highly ornamental and medicinal values. However, the phylogenetic relationship of Phaius among Calanthe s. l. has been highly debated based on morphological and molecular data. The complete chloroplast (cp) genome has been widely used as a useful molecular marker for resolving phylogenetic problems, while few genomic data on Phaius was available. Therefore, complete cp genomes of eight Phaius species were sequenced and characterized in detail to provide a better understanding of its phylogenetics in Calanthe s. l. Results The cp genomes of eight species investigated exhibited conserved quadripartite structures with varied lengths ranging between 157,997 bp to 158,735 bp. The overall GC content of these genomes ranged between 36.82 and 36.97%. Gene annotation revealed 136 genes in all eight genomes, of which 21 were duplicated in inverted regions and 15 with introns. Comparative analysis of eight cp genomes revealed stable sequence identity with greater variation in the single-copy regions, alongside notable differences in the genes at the LSC/IRb and IRb/SSC junctions, as well as in the number of SSRs. The phylogenetic analysis based on CDS from 49 complete cp genomes of Collabieae indicated that the eight Phaius species, together with other two species P. philippinensis and P. hainanensis, were clustered into a monophyletic clade among Calanthe s. l. and divided into two subclades with strong supports. Additionally, it was also supported that Calanthe s. l. should be divided into five genera with strong supports, including Calanthe s. s., Cephalantheropsis, Styloglossum, Phaius, and Preptanthe. Conclusions It was the first report on the complete cp genome of six Phaius species (P. columnaris, P. mishmensis, P. takeoi, P. tonkinensis, P. wallichii and P. wenshanensis) and has been comparatively analyzed in detail with P. flavus and P. tancarvilleae. It provided a comprehensive investigation of various cp genomic features for phylogenetic implications, including overall genome structure, codon usage, repeat sequences, IR boundaries, DNA polymorphisms, and phylogenetic reconstruction. It was suggested that Phaius and Calanthe s. s. should be treated as two independent genera. The concept of new genus Paraphaius was not confirmed by complete cp genomic data here. The intergeneric relationship of Phaius and its alliance in Calanthe group could be understood better by more cp genomic data.